Solidification process and effect of thermal treatments on Ni–Co–Mn–Sn metamagnetic shape memory alloys. (July 2015) - Pérez-Sierra, A.M.; Pons, J.; Santamarta, R.; Vermaut, P.; Ochin, P.
Abstract: The solidification process of three metamagnetic Ni–Co–Mn–Sn alloys has been investigated by DTA and DSC calorimetry, X-ray diffraction, optical and electron microscopy. The as-cast microstructures are composed of three phases: austenite L21 /6-layered martensite, D03 phase and γ phase (disordered fcc). Subsequent annealing treatments at 900 °C completely dissolve the D03 phase in the three alloys and also the γ phase in alloys with low Co content (6.4 and 7.2 at.%). However, for 9 at.% Co the stability of γ -phase extends to temperatures close to the melting point and becomes very sensitive to the Mn and Sn content. No traces of the B2–L21 order–disorder transition have been obtained in the alloys investigated. The multiphase solidification can be interpreted as a peritectic process where D03 is the primary solidified phase with dendritic growth, followed by the peritectic reaction of this phase with the residual liquid to form the austenite L21, whereas the γ -phase precipitates from the austenite L21 upon further cooling.